The existential phenomenological juvenile infant clinical: a review of Brazilian integrative literature (Phenomenology, Humanities and Sciences, 2023)
This work aimed to comprehend in Brazilian literature how the existential phenomenological clinic understands and attends to childhoods and teenagers. Therefore, a systematic literature review was accomplished in the Scielo, Bvs-Psi and Pepsic databases The research focus in academic articles published between 2000 and 2020. Twelve articles were selected for further analysis. The articles provided a look at childhood without delimiting the periods, the a priori markers, considering that children and adolescents are always in relation to their context. With regard to care, mediation, the phenomenological method and play therapy were appointed as therapeutic resources. The results point to the need for more publications on the subject, mainly related to the adolescent audience in which only two articles were found, as well as the possibility of conducting empirical studies.
Keywords: Existential phenomenology; Gestalt therapy; Children's clinic; Childhood and adolescence